Quantum Device: Empirical Modelling Of The Resonant Tunneling Diode - Ahmad, Anis Syarliza (2016)

(untitled)
The transistor was widely employed in integrated circuit design. Nevertheless, the continued scaling the transistor size will affect the device performances. RTD is an efficient high-speed device and has high-frequency operation up to Terahertz (THz) compared to the transistor. It has the potential to replace the transistor in the ultra-high frequency device applications in the future. Furthermore, RTD is a low power consumption device that works at low power compared to the transistor. Low power consumption needs to consider in integrated circuit design to have highest dynamic performance. This study will be modelled two different material system of RTD, which is GaAs/AlAs and In0.8Ga0.2As/AlAs. The physic-based equation will be simulated in MATLAB and the circuit model will be built up in LT Spice IV.Empirical fitting will be done in MATLAB to match the model to the experimental data. Meanwhile, in LT Spice IV, two methods were employed to simulate the circuit model, which are Table simulation and Polynomial simulation. The empirical fitting had been successfully matched the model to the experimental of GaAs/AlAs and In0.8Ga0.2As/AlAs. Based on results analysis, Table simulation had been successfully simulated I-V characteristics of experimental GaAs/AlAs and In0.8Ga0.2As/AlAs better than Polynomial simulation.